ADDITIVE NEUROPROTECTIVE EFFECT OF 3-HYDROXYPYRIDINE DERIVATIVES AND HUMAN ERYTHROPOETIN ANALOGUE ON A HEMORRHAGIC STROKE MODEL IN RATS - P. D. Kolesnichenko; O. V. Scheblykina; N. I. Nesterova; D. V. Scheblykin; A. V. Nesterov; M. V. Pokrovskiy; M. A. Zhuchenko; A. V. Tverskoy; K. M. Reznikov (Фармация и фармакология (Пятигорск), 2020)
The correction of free radical oxidation processes is one of the most promising strategies of neuroprotection in acute cerebrovascular disorders.The aim of the study is an experimental study of the neuroprotective effects of 3-hydroxypyridine and erythropoietin derivatives, as well as their combined use.Materials and methods. The study was performed on 109 male Wistar rats. The neuroprotective effect of the substances was studied on a hemorrhagic stroke model. The study drugs were administered to the animals intraperitoneally. Carbamylated darbepoetin was administered three times in advance at the dose of 100 µg/kg within intervals of 3 days, the last injection took place 1 hour before the operation (the total dose was 300 mg/kg). Etoxidol was administered once 1 hour before the surgery at the dose of 50 mg/kg. The survival rate, behavioral features and the state of the animals on the 1st, 3rd, 7th and 14th days were recorded, and the morphological assessment of the brain was carried out.Results. The investigated substances had a positive effect on both the survival rate of the animals during the first day and on the 14th day. The best survival rates on the 14th day were recorded in the group of a combined use of ethoxydol and carbamylated darbepoetin (75%). Thus, in this group of rats, a faster recovery of neurological disorders was already distinguished from the first day on. By the 7th day, more than 50% of the rats receiving the combination of the studied drugs, had had a slight neurological deficit (up to 3 points on the McGrow scale); by the 14th day there had been only minor changes in the neurological status in the rats of this group. A pronounced neuroprotective effect of the combination of 3-hydroxypyridine and erythropoietin derivatives has been confirmed by a histological examination of brain slices – a more rapid decrease in the size of perifocal edema and microcirculation disorders, less damage to neurons and glial elements, and faster processes of resorption and organization of hemorrhage. A macroscopic examination of the brain sections stained with triphenyltetrazolium chloride of the dying rats, showed that perifocal necrosis had been the main cause of high mortality in the control group after the 3rd day.Conclusion. As a result of the experiment, the nephroprotective effect of the studied derivatives of 3-hydroxypyridine and erythropoietin has been proved. Moreover, the combination of these drugs has shown a greater neuroprotective activity than their isolated use. The additive effect of these drugs was due to their action mechanism resulting from the synergism of various structures and components of the cells.